2001
DOI: 10.1046/j.1600-6135.2001.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Spectrum of Polyoma Virus Disease in Renal Allografts: Diagnostic Accuracy of Urine Cytology

Abstract: The morphological features of polyoma virus disease (PVDz) in 571 concurrent urine and biopsy samples from 413 patients are described. In 54 patients PV was found in both biopsy and urine samples. Histologically, PV presented as: (a) mild, viral cytopathic/cytolytic changes, with absent or minimal inflammation involving isolated tubules; (b) moderate and severe, cytopathic/cytolytic changes associated with patchy or diffuse tubulo-interstitial inflammation and atrophy; (c) advanced, graft sclerosis with rare o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
4

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(113 citation statements)
references
References 20 publications
3
106
0
4
Order By: Relevance
“…Taken together, these observations argue in favor of a caveolae-mediated endocytosis as the major route for BKV infectious entry [71]. In-support of the experimental evidence, ultrastructural analysis of BKV-infected renal tissue revealed that BK virions were localized to smooth, flask-shaped invaginations of the plasma membrane, which correspond to caveolae [72,73]. Conversely, JCV enters the target cell rapidly and requires proper assembly of clathrin-coated pits.…”
Section: Mechanisms Of Entry and Intracellular Traffickingmentioning
confidence: 64%
See 1 more Smart Citation
“…Taken together, these observations argue in favor of a caveolae-mediated endocytosis as the major route for BKV infectious entry [71]. In-support of the experimental evidence, ultrastructural analysis of BKV-infected renal tissue revealed that BK virions were localized to smooth, flask-shaped invaginations of the plasma membrane, which correspond to caveolae [72,73]. Conversely, JCV enters the target cell rapidly and requires proper assembly of clathrin-coated pits.…”
Section: Mechanisms Of Entry and Intracellular Traffickingmentioning
confidence: 64%
“…Viruses take advantage of the endocytic machinery to gain access to the cytosol and/or the nucleus of the target cell, where their replication and multiplication take place. BKV and JCV employ different internalization mechanisms to enter the host cell [69][70][71][72]. Dissection of the early events in the BKV lifecycle revealed that the virus enters cells by caveolae-mediated endocytosis.…”
Section: Mechanisms Of Entry and Intracellular Traffickingmentioning
confidence: 99%
“…Urine cytology is inexpensive and simple, but its shortcoming is a high false-positive rate. However, according to the literature, the false-positive rate and positive predictive value of urine cytology are reported differently [2, 3], and these differences probably result from the rigorous protocols for early detection of PVN. It has been reported that urine PV proliferation (PV viruria) appears 4 weeks to several months prior to viremia [4, 5] and appears 12 weeks earlier than PVN [3, 6].…”
Section: Discussionmentioning
confidence: 99%
“…2A). A retrospective immunohistological stain with anti-BK virus antibody (a mouse monoclonal anti-BK virus large T antigen antibody; Cemicon) showed some positive nuclei in the tubular epithelium, while there was a lack of virally induced epithelial cell lysis, presenting as typical stage A according to Drackenberg's classifi cation 5 (Fig. 2B).…”
Section: Case Reportmentioning
confidence: 99%